(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The role of women has undergone significant transformations throughout history, with various stages of development shaping their position in society. From the initial restrictive and oppressive conditions to the current state of empowerment and equality, the journey of women’s development has been marked by numerous milestones. This article will delve into the various stages of development of the role of women, highlighting their struggles, achievements, and the gradual shift towards gender equality.